2018
DOI: 10.1177/0825859718810718
|View full text |Cite
|
Sign up to set email alerts
|

Engaging the African American Church to Improve Communication About Palliative Care and Hospice: Lessons From a Multilevel Approach

Abstract: Background: As the spiritual family for many African Americans, the church presents an opportunity to improve communication about palliative care and hospice (PCH). However, sustainable change in church-based, practices related to PCH requires a compreshensive, multilevel approach. Objectives: Our primary goal was to encourage churches to embrace palliative care and hospice as acceptable alternatives for end-of-life care by creating venues to improve communications about PCH. This paper compares our experience… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
48
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(48 citation statements)
references
References 25 publications
(56 reference statements)
0
48
0
Order By: Relevance
“…Because faith leaders are familiar with key personnel, procedures, and lay members of the religious organization, they can help the initiative get off the ground and encourage wider member participation and commitment. Partnering with five primarily African American churches in the Philadelphia region, Johnson and colleagues 31 worked with faith communities to develop a leadership education program for pastors, ministry leaders, and other church leaders; establish a training program for lay companions; and distribute education materials about EOL decision-making. Using a church-based health promotion model, Johnson and colleagues found that head pastors were critical for project start-up and implementation, and the most successful lay-companion training program was headed by a pastor who regularly attended leadership education and lay-companion training sessions.…”
Section: Findings From Review Of Studies: Derivation Of Themesmentioning
confidence: 99%
“…Because faith leaders are familiar with key personnel, procedures, and lay members of the religious organization, they can help the initiative get off the ground and encourage wider member participation and commitment. Partnering with five primarily African American churches in the Philadelphia region, Johnson and colleagues 31 worked with faith communities to develop a leadership education program for pastors, ministry leaders, and other church leaders; establish a training program for lay companions; and distribute education materials about EOL decision-making. Using a church-based health promotion model, Johnson and colleagues found that head pastors were critical for project start-up and implementation, and the most successful lay-companion training program was headed by a pastor who regularly attended leadership education and lay-companion training sessions.…”
Section: Findings From Review Of Studies: Derivation Of Themesmentioning
confidence: 99%
“…14 The African American Church presents a venue to respond to this need. 26 As members of the spiritual family of the persons they visit, African American, church-based LHWs can offer spiritual support while also communicating about the range of issues rel-evant to ACP and end-of-life decision-making. 1,2,26,27 In addition, when LHWs are linked to their church community, the imprimatur of the church creates a receptive environment in which the LHWs can conduct their work.…”
Section: Introductionmentioning
confidence: 99%
“…African American Church members have expressed interest in education and training about communication with persons with life-limiting illnesses. 26,27 However, no curriculum exists to train African American, churchbased LHWs for the primary role of communicationsfacilitators, serving persons who have reached the stage of a life-limiting illness, and such training presents some unique challenges. First, such an undertaking should be buttressed by church partnerships, in contrast to partnering with church members as individuals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations